Vapor-Deposited Polymer Films and Structure: Methods and Applications - Chou, Fang-Yu; Ramli, Theresia Cecylia; Lee, Chin-Yun; Hu, Shu-Man; Christy, Jane; Chen, Hsien-Yeh (Organic Materials, 2023)
Vapor deposition of polymers is known to result in densified thin films, and recent developments have advanced these polymers with interesting fabrication techniques to a variety of controlled structures other than thin films. With the advantages of chemical modification and functionalization of these polymers, advancements have combined both the physical and chemical properties of these vapor-deposited polymers to obtain controlled anisotropic polymers, including layer-by-layer, gradient, hierarchical, porosity, and the combination of the above, meaning that the produced polymers are functional and are addressed in devised physical configurations and chemical compositions. The main purpose of using polymer coatings as a tool for surface modification is to provide additional properties that decouple the natural properties of the underlying materials (including metals, polymers, oxides/ceramics, glass, silicon, etc.), and recent advancements have rendered novel insights into combined physical and chemical properties to fulfill the increasing needs of sophisticated requirements of materials for users. The review herein intends to deliver messages of recent progress of the advancements of vapor-deposited polymers, with discussions of the variations of the physical structures and chemical functionalities, and how these two aspects are integrated with novel fabrication techniques. The advanced vapor polymers now have the capability of controlled anisotropy in the physical structure and chemical composition and are expected to pave the way for interface engineering toward prospective material designs.Table of content:1. Introduction2. Fabrication and Materials3. Controls of Anisotropy4. Applications5. Conclusions and Outlook
Keywords: vapor deposition; polymer coating; surface modification; surface structures; material interfaces